The gospel of the son of God: an introduction to Matthew - Bauer, David R. (InterVarsity Press, 2019)
From beginning to end, the Gospel of Matthew emphasizes that Jesus is the Son of God. In this comprehensive introduction to Matthew, David Bauer presents a holistic inductive approach with a literary, theological, and canonical focus. Exploring issues of genre, interpretive methods, authorship, audience, and literary structure, he also guides readers through interpretation and emerging theological themes.